Pengaruh Minat Baca dan Ketersediaan Sumber Belajar terhadap Prestasi Belajar - Anita Candra Dewi (P3I Luwu Raya, 2022)
The key to reading is the availability of learning resources and learning outcomes. The rapid development of an increasingly modern era demands the presence of qualified personnel. Improving the quality of personnel is an absolute prerequisite for achieving development goals. Therefore, the Indonesian government is currently focusing on development towards education that supports future life. In the era of globalization, quality human resources are very important. Therefore, the importance of education in the era of globalization must be considered to further motivate them to learn. In addition, education is a means to achieve national goals, in accordance with Article 31 (UUD 19).